Метод розширення набору модулів модифікованої досконалої форми системи залишкових класів - Касянчук, Михайло Миколайович; Якименко, Ігор Зіновійович; Івасьєв, Степан Володимирович; Маслияк, Богдан Олексійович (Kamianets-Podilskyi National Ivan Ohiienko University, 2017)
Present work declaring the method of expansion set of modules of modified perfect form of residual classes' system. It was shown that depends on their choice the bit of numbers, arithmetic operations performed over-their, was reduced by 2–3 times. This is especially necessary in the calculation of multi-digital numbers.